Penerapan Full Day School dalam Membentuk Karakter Religius Siswa - Juli Amaliya Nasucha; Ulfun Khoirotun; Elly Rachmawati; Moch. Kalam Mollah; Mo'tasim Mo'tasim (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
Nowadays, the phenomenon of the full day school program is quite attractive to the public. Full day school seems to answer all the concerns of parents who are no longer able to protect their children from negative behavior such as juvenile delinquency, drugs, brawls, and gadget addiction. This study aims to analyze the application of full day school in shaping the religious character of students at Raudhatul Jannah Pepelegi Junior High School, Waru Sidoarjo. This qualitative research found that the full day school program at the institution not only offers a system that combines general science and religious knowledge, but also includes additional study hours. Full day school tries to shape the religious character of students both in their devotion to God Almighty and in the practice of their social life. Full Day School is in line with the Islamic epistemology of Bayani, Irfani, and Burhani about the combination of intellectual and spiritual intelligence. Raudhatul Jannah Junior High School as an institution that implements a full day school program so far has been able to shape the religious character of its students through habituation activities as well as in religious activities held in schools. This success is due to the role of teachers as good role models and the cooperation of parents.